Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0047357
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine or Chloroquine-PI3K/Akt Pathway Inhibitor Combinations Strongly Promote γ-Irradiation-Induced Cell Death in Primary Stem-Like Glioma Cells

Abstract: We asked whether inhibitors of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, which is highly active in cancer stem cells (CSCs) and upregulated in response to genotoxic treatments, promote γ-irradiationγIR)-induced cell death in highly radioresistant, patient-derived stem-like glioma cells (SLGCs). Surprisingly, in most cases the inhibitors did not promote γIR-induced cell death. In contrast, the strongly cytostatic Ly294002 and PI-103 even tended to reduce it. Since autophagy was induced we examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 46 publications
4
75
0
1
Order By: Relevance
“…Previous reports have suggested that autophagy-related protein plays an important role during the encystation of Acanthamoeba cells (19,23). In this study, we found that autophagy inhibitors 3MA and chloroquine significantly reduced the encystation ratio of Acanthamoeba cells.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous reports have suggested that autophagy-related protein plays an important role during the encystation of Acanthamoeba cells (19,23). In this study, we found that autophagy inhibitors 3MA and chloroquine significantly reduced the encystation ratio of Acanthamoeba cells.…”
Section: Discussionsupporting
confidence: 65%
“…Chloroquine is widely used as an antimalarial drug that interferes with hemozoin formation (27). Currently, the most widely used autophagy inhibitor is chloroquine (23,28). Chloroquine is a well-known antimalarial drug in clinical use (29).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously showed that radiotherapy triggers an inflammation response as well as TGF-β expression [38]. Therefore, exploiting the radiosensitizing property of CQ could improve responses obtained by radiation treatments, as was observed in other studies [46,47]. Moreover, acknowledging that GBM typically depict resistance to standard chemotherapeutics, one could argue that adding CQ might hinder this other malignant glioma characteristic.…”
Section: Discussionmentioning
confidence: 81%
“…Following a first observational study that reported an inhibitory effect of chloroquine on the pancreatic cancer cell line PaTu II (12), the effects of chloroquine on tumor growth were later confirmed in mouse models of PDAC and attributed to the inhibition of autophagy (13), which is responsible for recycling bioenergetic components to ensure cell survival in nutrient-deprived times or locations (13). For breast cancer and glioblastoma, chloroquine has been suggested to also have an impact on the cancer stem-like phenotype via inhibition of autophagy (14,15). However, it has recently been suggested that chloroquine may also function as an inhibitor of CXCR4 signaling (16).…”
Section: Introductionmentioning
confidence: 98%